2017
DOI: 10.1038/nature25158
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-derived ASC specks cross-seed amyloid-β in Alzheimer’s disease

Abstract: The spreading of pathology within and between brain areas is a hallmark of neurodegenerative disorders. In patients with Alzheimer's disease, deposition of amyloid-β is accompanied by activation of the innate immune system and involves inflammasome-dependent formation of ASC specks in microglia. ASC specks released by microglia bind rapidly to amyloid-β and increase the formation of amyloid-β oligomers and aggregates, acting as an inflammation-driven cross-seed for amyloid-β pathology. Here we show that intrah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
640
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 758 publications
(677 citation statements)
references
References 33 publications
30
640
2
5
Order By: Relevance
“…Elegant work demonstrated that aggregated Aβ displaying amyloid structure [38, 55] activates the NLRP3–ASC inflammasome, following endo-lysosomal uptake and damage [38], resulting in the activation of caspase-1, subsequent cleavage of pro-IL-1β to IL-1β, and microglial activation [38]. NLRP3 inflammasome assembly was subsequently demonstrated to actively contribute to amyloid pathology [42, 95]. Heneka et al elegantly demonstrated that inflammasome inhibition through NLRP3 or caspase-1 deficiency inhibits amyloid pathology in APP/PS1 transgenic mice [42, 95], with alterations in microglial phenotypes and phagocytosis capacity as potential contributing mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Elegant work demonstrated that aggregated Aβ displaying amyloid structure [38, 55] activates the NLRP3–ASC inflammasome, following endo-lysosomal uptake and damage [38], resulting in the activation of caspase-1, subsequent cleavage of pro-IL-1β to IL-1β, and microglial activation [38]. NLRP3 inflammasome assembly was subsequently demonstrated to actively contribute to amyloid pathology [42, 95]. Heneka et al elegantly demonstrated that inflammasome inhibition through NLRP3 or caspase-1 deficiency inhibits amyloid pathology in APP/PS1 transgenic mice [42, 95], with alterations in microglial phenotypes and phagocytosis capacity as potential contributing mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…NLRP3 inflammasome assembly was subsequently demonstrated to actively contribute to amyloid pathology [42, 95]. Heneka et al elegantly demonstrated that inflammasome inhibition through NLRP3 or caspase-1 deficiency inhibits amyloid pathology in APP/PS1 transgenic mice [42, 95], with alterations in microglial phenotypes and phagocytosis capacity as potential contributing mechanisms. These findings were further confirmed using pharmacological NLRP3 inhibitors [16, 19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of microglia in CNS development is clear due to the fact that the CNS incorporates several disintegrations in the case of malfunctioning of the mutation-induced microglial cells [12, 13]. As CNS-resident macrophages have many features of innate immune responses, such as the secretion of pro- and anti-inflammatory cytokines, nitric oxide, and expression of many receptors (i.e., TLRs) [14], microglia are involved in nearly all CNS diseases in which we could see inflammation or degeneration, such as Alz­heimer’s disease [15], multiple sclerosis [16], and Parkinson diseases [17]. …”
Section: Introductionmentioning
confidence: 99%